2017
DOI: 10.1126/science.aal1727
|View full text |Cite
|
Sign up to set email alerts
|

Satellites reveal contrasting responses of regional climate to the widespread greening of Earth

Abstract: Changes in vegetation cover associated with the observed greening may affect several biophysical processes, whose net effects on climate are unclear. We analyzed remotely sensed dynamics in leaf area index (LAI) and energy fluxes in order to explore the associated variation in local climate. We show that the increasing trend in LAI contributed to the warming of boreal zones through a reduction of surface albedo and to an evaporation-driven cooling in arid regions. The interplay between LAI and surface biophysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
239
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 323 publications
(257 citation statements)
references
References 52 publications
15
239
2
1
Order By: Relevance
“…While semi-arid ecosystems of eastern Africa might play a smaller role than Australian ones (simply due to the difference in the area they cover), it would still influence the magnitude and trend of the global carbon sink by terrestrial ecosystems. Furthermore, Forzieri et al (2017) report the importance of the interplay between vegetation cover (in terms of leaf area index, LAI) and surface biophysics, finding an amplification of their relationship under extreme warm-dry and cold-wet years. Here we found that the ENSO contribution impacts the temporal LAI variability in eastern Africa considerably (Fig.…”
Section: Present-day Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…While semi-arid ecosystems of eastern Africa might play a smaller role than Australian ones (simply due to the difference in the area they cover), it would still influence the magnitude and trend of the global carbon sink by terrestrial ecosystems. Furthermore, Forzieri et al (2017) report the importance of the interplay between vegetation cover (in terms of leaf area index, LAI) and surface biophysics, finding an amplification of their relationship under extreme warm-dry and cold-wet years. Here we found that the ENSO contribution impacts the temporal LAI variability in eastern Africa considerably (Fig.…”
Section: Present-day Simulationsmentioning
confidence: 99%
“…A5), presenting a good example of such temporal variations that can play significant roles in modulating key vegetation-climate interactions. According to the analysis by Forzieri et al (2017), the magnitudes of differences we found in our study due to accounting for an intensified ENSO signal are influential on the surface energy balance components such as longwave outgoing radiation, latent heat flux, and sensible heat flux. Our findings reiterate the importance of considering ENSO contribution in carbon and energy budget calculations for any region that is influenced by ENSO variability.…”
Section: Present-day Simulationsmentioning
confidence: 99%
“…In return, changes in vegetation dynamics may affect local climate via several biophysical processes, leading to positive or negative feedback in the land-climate system [16,17]. For instance, Forzieri, G. et al [18] showed that positive trend in LAI contributed to the warming of boreal zones and to a cooling in arid regions. The impacts of climate change on the vegetation dynamics and their potential interactions have been increasingly studied, given their possible benefits in carbon sequestration [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Forests cover more than~42 million km 2 in the Northern Hemisphere (~30% of the land surface), and affects local climate mainly through biophysical processes [1][2][3][4]. The biophysical processes (e.g., albedo, evapotranspiration rate (ET) and surface roughness) all have effects on surface energy fluxes, which causes the effects of forests on local climates to be complicated [5].…”
Section: Introductionmentioning
confidence: 99%